1992
DOI: 10.1111/j.1574-6968.1992.tb05243.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of aSerpula (Treponema) hyodysenteriaehemolysin gene by homologous recombination: Importance of this hemolysin in pathogenesis ofS. hyodysenteriaein mice

Abstract: The role of Serpula hyodysenteriae hemolysin in the pathogenesis of swine dysentery was studied. The inactivation of a gene, tly, encoding a hemolysin, and the virulence of a tly− mutant in mice is reported. We obtained chromosomal integration of the distrupted tly gene via homologous recombination in a S. hyodysenteriae wild‐type strain following electroporation. A plasmid construct, in which the tly gene was disrupted by a kanamycin‐resistance gene, was used for the electroporation. The mutants obtained had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
(6 reference statements)
0
22
0
Order By: Relevance
“…To date, only the kanamycin gene has been reported to be functional as a genetic marker in S. hyodysenteriae (59). We have demonstrated that the cat marker is an alternative to kan, and the availability of two functional genetic markers in S. hyodysenteriae will be of great utility in the construction of defined mutants altered in more than one genetic locus.…”
Section: Discussionmentioning
confidence: 93%
“…To date, only the kanamycin gene has been reported to be functional as a genetic marker in S. hyodysenteriae (59). We have demonstrated that the cat marker is an alternative to kan, and the availability of two functional genetic markers in S. hyodysenteriae will be of great utility in the construction of defined mutants altered in more than one genetic locus.…”
Section: Discussionmentioning
confidence: 93%
“…Transferring genes into S. hyodysenteriae cells by electroporation to form stable recombinants has been accomplished (23,31). From these experimental results, 500 ng of total DNA, consisting of plasmid and construct DNA (S. hyodysenteriae gene disrupted with an antibiotic resistance gene), was electroporated into 10 10 cells to obtain five recombinants.…”
Section: Discussionmentioning
confidence: 99%
“…Three S. hyodysenteriae genes conferring hemolytic activity to transformed Escherichia coli have been cloned (23,24). One of these genes was further characterized and designated tly (34). For convenience these genes will be (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic exchange between S. hyodysenteriae cells has not been reported, and only recently has this bacterium been transformed (34). Therefore, classical genetic studies, which have often proved useful for studying the genetics of pathogenicity in many bacteria, have not been applied to S. hyodysenteriae.…”
mentioning
confidence: 99%